2016
DOI: 10.7567/jjap.55.08pb02
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching characteristics in memristors with Al2O3/TiO2 and TiO2/Al2O3 bilayers

Abstract: bilayer structures, fabricated by atomic layer deposition at 200°C and post-deposition annealing, were studied in Pt bottom electrode (Pt-BE)/insulator/Pt top electrode (Pt-TE) capacitors. The Pt-BE/ Al 2 O 3 /TiO 2 /Pt-TE capacitor exhibits stable bipolar resistive switching with an on-resistance/off-resistance ratio of >10 2 controlled by a small voltage of +0.8 V. The forming process occurs in two steps of breaking of the Al 2 O 3 layer and transfer of oxygen vacancies (V O ) into the TiO 2 layer. The capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
11
0
3
Order By: Relevance
“…利点から 1) ,Flash のブロッキング層 2,3) ,ReRAM のスイ ッチング層 4,5) ,DRAM の絶縁膜層 6,7) ,GaN パワーデバ いられ,Si 半導体の分野では Si/SiO2 界面における SiO2 Al2O3…”
Section: は じ め にunclassified
“…利点から 1) ,Flash のブロッキング層 2,3) ,ReRAM のスイ ッチング層 4,5) ,DRAM の絶縁膜層 6,7) ,GaN パワーデバ いられ,Si 半導体の分野では Si/SiO2 界面における SiO2 Al2O3…”
Section: は じ め にunclassified
“…In all cases, the origin of switching has been attributed to either the drift of oxygen vacancies 28 and/or interstitials 29 or the formation of conductive filaments 30 within an active metal-oxide core under the influence of an applied electrical field. Within that context several studies have reported on the importance of interface interactions and properties 31 , showing that the introduction of a thin interfacial barrier layer between the active layer and one of the electrodes can influence the electrochemical processes, the devices’ stability 32 , 33 , improve its switching characteristics and reduce the overall power consumption 34 – 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed an approach to design thin-film TiO 2 /Al 2 O 3 bilayer structures [14,15], exhibiting electric-field analog tuning of the nonvolatile resistance state in the range of seven orders of magnitude. Despite a wide memory window and the existence of multiple nonvolatile resistance states, TiO 2 /Al 2 O 3 bilayer structures demonstrate nonlinear behavior originating from the initial difference in the resistive properties of TiO 2 and Al 2 O 3 layers.…”
Section: Introductionmentioning
confidence: 99%